2000
DOI: 10.1128/aem.66.8.3368-3375.2000
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of thep-Coumarate Decarboxylase Gene fromLactobacillus plantarumReveals the Existence of Two Other Inducible Enzymatic Activities Involved in Phenolic Acid Metabolism

Abstract: Lactobacillus plantarum NC8 contains a pdc gene coding for p-coumaric acid decarboxylase activity (PDC). A food grade mutant, designated LPD1, in which the chromosomal pdc gene was replaced with the deleted pdc gene copy, was obtained by a two-step homologous recombination process using an unstable replicative vector. The LPD1 mutant strain remained able to weakly metabolize p-coumaric and ferulic acids into vinyl derivatives or into substituted phenyl propionic acids. We have shown that L. plantarum has a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 45 publications
6
101
1
3
Order By: Relevance
“…In order to investigate alternate pathways for phenolic acid degradation, a L. plantarum strain deficient in PDC activity was constructed [2]. The procedure used led to a completely stable chromosomal deletion within the pdc gene through a two-step homologous recombination process.…”
Section: Phenotypic Analysis Of the L Plantarum Strain Deficient In mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate alternate pathways for phenolic acid degradation, a L. plantarum strain deficient in PDC activity was constructed [2]. The procedure used led to a completely stable chromosomal deletion within the pdc gene through a two-step homologous recombination process.…”
Section: Phenotypic Analysis Of the L Plantarum Strain Deficient In mentioning
confidence: 99%
“…Kinetic reactions were started by addition of the substrate and samples were diluted in Stop buffer. Phenolic acid consumption and derivative production was monitored by UV-spectrophotometry scanning (from 180 to 330 nm using quartz cuvettes in a Beckman DU600 spectrophotometer) as previously described [2,5,13]. bacteria grown with these substrates suggesting that this activity was inducible.…”
Section: Preparation Of Whole Cell Suspensions Cell-free Extracts Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Most Lactobacillus spp. are unable to degrade polyphenols, but strains of the closely related species Lactobacillus plantarum, Lactobacillus pentosus and Lactobacillus paraplantarum possess tannase activity (14) -tannins are naturally occurring water soluble polyphenols -and metabolise phenolic acids (15).…”
Section: Introductionmentioning
confidence: 99%
“…Chambel et al (11) showed that Saccharomyces cerevisiae induced the expression of the H ϩ -ATPase pumps in response to inhibitory concentrations of cinnamic acid. In a previous work (4), we demonstrated that the ubiquitous lactic acid bacterium Lactobacillus plantarum exhibits inducible pcoumaric acid decarboxylase (PDC) activity, which converts p-coumaric acid into 4-vinyl phenol, a less toxic compound. We also showed that L. plantarum PDC activity confers a selective advantage for growth in p-coumaric acid-supplemented medium and therefore proposed that PDC synthesis could be considered as a stress response induced by phenolic acid toxicity.…”
mentioning
confidence: 99%